2021
DOI: 10.1590/1519-6984.220259
|View full text |Cite
|
Sign up to set email alerts
|

Phytochemical characterization, antioxidant potential and antimicrobial activity of Averrhoa carambola L. (Oxalidaceae) against multiresistant pathogens

Abstract: The objective of this work was to perform the phytochemical characterization, to determine total phenols, antioxidant (AAO%) and antimicrobial potential of the ethanolic extracts of carambola. The phytochemical study was carried out through a qualitative analysis of the chemical constituents and quantitative determination of the phenol content By the Folin-Ciocalteu test. Qualitative and quantitative antioxidant tests were performed using the DPPH method (2,2 diphenyl-1-picryl-hydrazila) and iron reduction (FR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…The phytochemical studies on the extracts of Averrhoa carambola plant leaves, fruits, and roots showed a predominant content of saponins, flavonoids, alkaloids, tannins, and pyrogallic steroids (Khoo et al., 2010, 2016; Muthu et al., 2016). Other phytochemicals such as phenols, anthocyanin and anthocyanidin, chalcones and aurones, leucoanthocyanidins, catechins, and triterpenoids were also extracted from various parts of star fruit (Silva et al., 2020).…”
Section: Results and Discussion Of Trendsmentioning
confidence: 99%
“…The phytochemical studies on the extracts of Averrhoa carambola plant leaves, fruits, and roots showed a predominant content of saponins, flavonoids, alkaloids, tannins, and pyrogallic steroids (Khoo et al., 2010, 2016; Muthu et al., 2016). Other phytochemicals such as phenols, anthocyanin and anthocyanidin, chalcones and aurones, leucoanthocyanidins, catechins, and triterpenoids were also extracted from various parts of star fruit (Silva et al., 2020).…”
Section: Results and Discussion Of Trendsmentioning
confidence: 99%
“…Several previous studies have reported that scientifically Averrhoa carambola L. has potential in medicine, including anti-inflammatory and anti-tumor properties 67 , antioxidants 68 , antimicrobial 67 . The root of this plant is also proven to have antidiabetic activity.…”
Section: Resultsmentioning
confidence: 99%
“…The great interest around these classes of secondary metabolites is the correlation that these compounds have with various biological activities (Fonseca et al, 2019;Santos et al, 2018), such as antioxidant and antimicrobial activities among other (Silva et al, 2021;Kuhn et al, 2019;Mallmann et al, 2018). A diet abundant in some of these compounds is able to act in the prevention of various diseases.…”
Section: Phytochemical Prospectingmentioning
confidence: 99%